Informed Trading around Stock Split Announcements: Evidence from the Option Market - Gharghori, Philip; Maberly, Edwin D.; Nguyen, Annette (Journal of Financial and Quantitative Analysis, 2017)
Prior research shows that splitting firms earn positive abnormal returns and that they experience an increase in stock return volatility. By examining option-implied volatility, we assess option traders’ perceptions on return and volatility changes arising from stock splits. We find that they do expect higher volatility following splits. There is only weak evidence, though, of option traders anticipating an abnormal increase in stock prices. We also show that our option measures can predict both stock volatility levels and changes after the announcement. However, there is little evidence that they can predict the returns of splitting firms.